Evaluation of Aluminium Dross as Adsorbent for Removal of Carcinogenic Congo Red Dye in Wastewater - Mohamad Zulfika Hazielim, b Zakaria; Nur Syuhada, Ahmad Zauzi; Rubiyah, Baini; Norsuzailina, Mohamed Sutan; Md Rezaur, Rahman (IOP Publishing Ltd, 2017)
In this study, aluminium dross waste generated from aluminium smelting industries was employed as adsorbent in removing of congo red dye in aqueous solution. The raw aluminium dross as adsorbent was characterized using Scanning Electron Microscope (SEM), Brunauer-Emmett-Teller (BET) for surface area and X-Ray Fluorescence (XRF) Spectroscopy. Adsorption experiments were carried out by batch system at different adsorbent mass, pH, and initial dye concentration. The results showed that the per cent removal of dye increased as adsorbent mass increased. It was found that 0.4 gram of adsorbent can remove approximately 100 % of dye at pH 9 for dye concentration 20 and 40 ppm. Therefore, it can be concluded that raw aluminium dross without undergone any treatment can be effectively used for the adsorption of congo red in textile wastewater related industries.